2022
DOI: 10.1038/s41586-022-05369-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate cyclase activity of TIR1/AFB auxin receptors in plants

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 47 publications
4
59
1
Order By: Relevance
“…The application of carefully curated amino acid motifs to model and non-model organisms across the tree of life, therefore offers an exciting and currently undervalued opportunity for the discovery of hidden or unexpected ligand interacting sites in new and/or well-characterized proteins [107] , [164] . This is in addition to the many examples of enzymatic moonlighting sites already identified [25] , [27] , [32] , [36] .…”
Section: Conclusion: Establishing Interactomes and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of carefully curated amino acid motifs to model and non-model organisms across the tree of life, therefore offers an exciting and currently undervalued opportunity for the discovery of hidden or unexpected ligand interacting sites in new and/or well-characterized proteins [107] , [164] . This is in addition to the many examples of enzymatic moonlighting sites already identified [25] , [27] , [32] , [36] .…”
Section: Conclusion: Establishing Interactomes and Beyondmentioning
confidence: 99%
“…Discovering protein interactants beyond those involved in catalysis, could reveal novel signaling mechanisms or revisit existing ones [38] , [107] . One such example is the recent identification of an AC operating in the TIR1/AFB auxin receptors which participate in the classical nuclear auxin signal transduction pathway that affects auxin-dependent root growth inhibition and gravitropism [164] , [165] . A better understanding of interactomes is also likely to uncover complex hidden mechanisms that operate at a systems level [166] , [167] .…”
Section: Conclusion: Establishing Interactomes and Beyondmentioning
confidence: 99%
“…Sutherland et al first identified cAMP in 1956 and demonstrated it to be a second messenger in the liver, , Kandel further discovered that cAMP could switch short-term memory into long-term memory and relieve the fatigue of brain cells, , and they were awarded the Nobel Prize in Physiology or Medicine in 1971 and 2000, respectively. Subsequent studies showed that cAMP participates in a wide range of cell metabolism regulations and functions as an intracellular second messenger in a variety of organisms. In plants, cAMP has been demonstrated to function as a second messenger involved in pollen tube growth and reorientation in maize and root growth in Arabidopsis thaliana. , …”
Section: Introductionmentioning
confidence: 99%
“…Auxin regulates nearly every aspect of plant growth, development, and responses to the environment, and has been shown to control transcription-independent rapid responses occurring in seconds as well as slow transcriptional responses [1][2][3][4][5][6][7] . The latter requires the intracellular receptors TRANSPORT INHIBITOR RESPONSE 1 (TIR1)/AUXIN-SIGNALING F-BOX proteins (AFBs) that promote the degradation of their co-receptors AUX/IAA transcriptional repressors and act as adenylate cyclases [8][9][10][11][12][13] . Increasing studies show that many auxin-induced effects such as plasma-membrane hyperpolarization, cytosolic Ca 2+ -transients, activation of ROP GTPases, RAF-like kinase-dependent cytoplasmic streaming, and protoplast swelling, are too rapid to depend on transcriptional regulation 5,7,[14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%